2022
DOI: 10.1002/msc.1615
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of clinical variables that enhance therapeutic alliance in patients seeking care for musculoskeletal pain: A mixed methods approach

Abstract: Introduction/Objectives Therapeutic alliance (TA) is an integral part of building a patient and clinician relationship. TA begins at the initial encounter; however, the specific TA behavioural practices that are most impactful and linked to pain reduction and improved function remain unclear. The primary objective of this study was to explore physical therapist behaviours and interactions during the initial physical therapy evaluation and how they related to the patient's perception of TA. A secondary objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…48 In addition to clinician knowledge, contextual factors such as therapeutic alliance and treatment expectations are also likely to influence a patients' engagement and acceptance of the information. A recent study by Myers et al, 50 concluded that a lack of PSE was associated with lower patient-perceived therapeutic alliance. Thus, experienced clinicians delivering PSE may facilitate a greater change in patient understanding and in doing so greater confidence in patients to enact the learning.…”
Section: Discussionmentioning
confidence: 97%
“…48 In addition to clinician knowledge, contextual factors such as therapeutic alliance and treatment expectations are also likely to influence a patients' engagement and acceptance of the information. A recent study by Myers et al, 50 concluded that a lack of PSE was associated with lower patient-perceived therapeutic alliance. Thus, experienced clinicians delivering PSE may facilitate a greater change in patient understanding and in doing so greater confidence in patients to enact the learning.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies that have commented on the lack of contextual factor instruction in ELPT education have done so by gathering information from physical therapists about their abilities or their education experience. [23][24][25][26]35,[43][44][45] However, this is only one side of the coin. To the author's knowledge, this is the first study examining musculoskeletal faculty's perceptions of the therapeutic relationship and how that might influence the curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…A mixed method study investigated (1) how physical therapist behaviours and interactions during the initial physical therapy assessment relate to the patient's perception of WA and (2) the relationship between WA, pain intensity, and function [16]. Mayers and colleagues used (1) qualitative analysis to develop a checklist of WA themes and behavioural practices and (2) Spearman's Rho (ρ) to quantify if there was an association between increased WA and improved clinical outcomes [16]. Patient-rated WA was stronger when the physical therapists used information gathering, paused to listen, used humour and transitions, and used clarifying questions [16].…”
Section: Introductionmentioning
confidence: 99%
“…Mayers and colleagues used (1) qualitative analysis to develop a checklist of WA themes and behavioural practices and (2) Spearman's Rho (ρ) to quantify if there was an association between increased WA and improved clinical outcomes [16]. Patient-rated WA was stronger when the physical therapists used information gathering, paused to listen, used humour and transitions, and used clarifying questions [16]. Patient-rated WA was weaker when the following behavioural practices were present: lack of touch, the absence of pain neuroscience education, and not restating what the patient had said during the interview [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation